3D printing algorithm of anisotropic biological scaffold with oxidized nanocellulose and gelatin. Issue 14 (22nd September 2019) - Xu, Xiaodong; Zhou, Jiping; Feng, Chen; Jiang, Yani; Zhang, Qi; Shi, Hongcan
Abstract: Tissue scaffolds need to have anisotropic mechanical properties and a porous structure to meet the needs of different tissues and organs. This report presents results of a study on an especially-designed 3D printing method with oxidized nanocellulose and gelatin, analyzes the servo principle of pneumatic condensing extrusion 3D printer, and proposes a hexagonal algorithm. For the purpose of this study, a printing process file was written by G code, physical and mechanical performance of the 3D scaffolds was evaluated with Solidworks simulation, the porous structure and pressure-pull performance of the printed 3D scaffolds was observed by SEM, and experiments were conducted to measure their bio-compatibility. The study draws the conclusion that scaffolds thus printed have a highly porous structure and anisotropic mechanical properties.